A method for preparing high-frequency and high-speed BT resin-based copper-clad laminate
By using DBA modified hollow glass microspheres and bismaleimide-triazine resin in copper clad plates, the problem of poor dielectric performance of existing copper clad plates is solved, and good signal transmission and material performance improvement in high-frequency and high-speed applications are achieved.
Patent Information
- Application Number
- CN202411288266.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-14
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-09-14
AI Technical Summary
The existing copper clad plate has poor dielectric performance in high-frequency and high-speed applications, resulting in low signal fidelity, and the performance of the resin matrix limits the development of high-performance copper clad plate.
Bismaleimide-triazine resin (BT resin) is used as the resin matrix of copper clad plate, and the dielectric properties and toughness of the resin are improved by DBA modification of hollow glass microspheres.
It improves the dielectric properties and bending strength of copper clad plates, enhances the compatibility and interface bonding ability of resins, and reduces processing difficulty and cost.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of copper clad laminates, and in particular to a method for preparing a high-frequency and high-speed BT resin-based copper clad laminate. Background Art
[0002] Copper clad laminate, also known as copper clad laminate (CCL), is a plate-like material made by impregnating glass fiber cloth with resin, covering one or both sides with copper foil and hot pressing. It is the core substrate of printed circuit boards (PCB). With the continuous advancement of the electronic information industry, the demand for high-performance copper clad laminates that can meet the stable transmission of information is increasing. The transmission of signals depends to a large extent on the dielectric properties of the substrate. At the same frequency, the smaller the dielectric loss, the higher the fidelity of signal transmission. Therefore, it is of great significance to develop high-frequency and high-speed high-performance printed circuit boards with low dielectric constant and dielectric loss. The resin matrix has a decisive influence on many properties of copper clad laminates. The common epoxy resin matrix has poor dielectric properties, the polyphenylene ether resin matrix has high melt viscosity and poor processability, and the bonding performance of polytetrafluoroethylene resin is not high. These all restrict the development of high-performance copper clad laminates.
[0003] In summary, it is of great significance to solve the above problems and manufacture a high-frequency and high-speed BT resin-based copper clad laminate. Summary of the invention
[0004] The object of the present invention is to provide a method for preparing a high-frequency and high-speed BT resin-based copper-clad laminate to solve the problems raised in the above-mentioned background technology.
[0005] In order to solve the above technical problems, the present invention provides the following technical solutions:
[0006] A method for preparing a high-frequency and high-speed BT resin-based copper-clad laminate comprises the following steps:
[0007] Step 1: Preparation of DBA-modified hollow glass microspheres: (1) treating the hollow glass microspheres with sodium hydroxide solution and silane coupling agent to obtain modified hollow glass microspheres A; (2) mixing the modified hollow glass microspheres A, mercapto acid, and a photoinitiator, reacting under ultraviolet light, and then washing, and chlorinating the dried product to obtain modified hollow glass microspheres B; (3) adding the modified hollow glass microspheres B, aluminum chloride, and 2,2'-diallylbisphenol A to ethanol, and reacting to obtain DBA-modified hollow glass microspheres;
[0008] Step 2: Preparation of prepreg: (1) DBA-modified hollow glass microspheres, 2,2′-diallyl bisphenol A, bismaleimide, and bisphenol A cyanate are mixed, and a BT resin prepolymer is obtained after a temperature reaction is completed; (2) BT resin prepolymer, epoxy resin, curing agent, and curing accelerator are dissolved in a solvent to obtain a prepreg, and a glass fiber cloth is impregnated in the prepreg and then heated and cured to obtain a prepreg;
[0009] Step 3: Preparation of BT resin-based copper clad laminate: After laminating the prepregs in multiple layers, cover both sides with copper foil, press them in a vacuum press, and obtain a BT resin-based copper clad laminate after cooling.
[0010] Wherein, in step 1 (1), the concentration of the sodium hydroxide solution is 30-70%, the silane coupling agent is a vinyl silane coupling agent, and the mass ratio of the silane coupling agent to the hollow glass microspheres is (1-2):1;
[0011] Preferably, the vinyl silane coupling agent includes but is not limited to one of vinyl trimethoxy silane, vinyl triethoxy silane and vinyl tri-tert-butoxy silane;
[0012] Wherein, in step 1 (2), the specific process is: adding the modified hollow glass microsphere A and mercapto acid into dichloromethane, adding 0.1-0.8wt% of photoinitiator after dispersion, stirring evenly and irradiating with ultraviolet light for 10-60s, filtering and washing with ethanol, mixing the obtained product with thionyl chloride and N,N-dimethylformamide evenly, condensing and refluxing at 40-80°C for 8-16h, washing and drying to obtain the modified hollow glass microsphere B; wherein the mass ratio of the modified hollow glass microsphere A, mercapto acid, thionyl chloride and N,N-dimethylformamide is 1:(1-3):(20-30):(1-3);
[0013] Preferably, the mercapto acid includes but is not limited to one of 6-mercaptohexanoic acid and 8-mercaptooctanoic acid; the photoinitiator includes but is not limited to one of (2,4,6-trimethylbenzoyl) diphenylphosphine oxide (TPO) and ethyl 2,4,6-trimethylbenzoylphenylphosphonate (TPO-L);
[0014] Wherein, in step 1 (3), the specific process is: adding the modified hollow glass microsphere B to ethanol, after ultrasonic dispersion, adding aluminum chloride and 2,2'-diallyl bisphenol A, reacting at 40-60° C. for 10-15 hours, filtering, washing and drying to obtain DBA modified hollow glass microspheres; wherein the mass ratio of the modified hollow glass microsphere B, aluminum chloride and 2,2'-diallyl bisphenol A is (2-3): (1-1.5): (4-6);
[0015] Wherein, in step 2 (1), the specific process is: adding DBA modified hollow glass microspheres to acetone, adding 2,2′-diallyl bisphenol A after ultrasonic dispersion, stirring and ultrasonic dispersion for 1 hour, adding bismaleimide and bisphenol A type cyanate in sequence, heating until melted, raising the temperature to 120-180° C. and stirring continuously, reacting for 20-50 minutes, and obtaining a BT resin prepolymer; the mass ratio of the DBA modified hollow glass microspheres, 2,2′-diallyl bisphenol A, bismaleimide and bisphenol A type cyanate is (2-8): (4-8): (6-8): (10-15);
[0016] Wherein, in step 2 (2), by weight: 80-120 parts of BT resin prepolymer, 15-50 parts of epoxy resin, 5-15 parts of curing agent, 1-5 parts of curing accelerator, 10-30 parts of solvent; the glass fiber cloth is impregnated in the prepreg for 5-20 minutes; the curing temperature is 120-150° C., and the curing time is 2-5 hours;
[0017] Preferably, the curing agent includes one or more of dicyandiamide and phenolic resin; the curing accelerator is an imidazole accelerator; the solvent includes one of acetone, butanone, cyclohexanone and dimethylformamide;
[0018] Among them, in step three, the specific temperature and pressure during the pressing process are: raising the temperature and pressure to 150-160°C, 0.5-0.8Mpa, and maintaining for 1-1.5h, then raising the temperature and pressure to 170-190°C, 0.9-1.2Mpa, and maintaining for 1.5-2h, and finally raising the temperature and pressure to 190-220°C, 1.8-2.2Mpa, and maintaining for 1.5-2h.
[0019] Compared with the prior art, the beneficial effects achieved by the present invention are:
[0020] The present invention uses bismaleimide-triazine resin (BT resin) formed by copolymerization of bismaleimide and cyanate as the resin matrix of the copper clad laminate. The BT resin has good heat resistance and good dielectric properties. The dielectric constant of hollow glass microspheres is 1.2 to 2.2. By adding hollow glass microspheres to BT resin, the dielectric properties of the resin system can be further improved. However, hollow glass microspheres have problems such as difficulty in dispersion in the resin system, little interaction with the polymer matrix, and loose interface bonding.
[0021] Therefore, the present invention uses 2,2′-diallyl bisphenol A (DBA) to modify the surface of hollow microsphere glass. The specific principle is that the hollow microsphere glass is treated with a vinyl silane coupling agent to introduce vinyl groups, and carboxylic acids are introduced through addition with mercapto acid. Finally, DBA is grafted after chlorination to obtain DBA-modified hollow glass microspheres. The allyl group on the surface of the modified hollow microsphere glass can react with bismaleimide. While significantly improving the compatibility of the hollow microsphere glass with the resin system, DBA can play a chain extension role in the bismaleimide resin, thereby improving the toughness of the resin.
[0022] In addition, DBA can act as a catalyst in the cyanate triazine reaction, which can reduce the temperature required for cyanate triazine reaction, thereby reducing the difficulty of processing; hollow microsphere glass has a light specific gravity and a large volume, which can reduce the use of raw material resin and reduce costs; at the same time, the gas filled inside the hollow microsphere glass can improve the flame retardancy and thermal insulation properties of the material, and can reduce the amount of flame retardant in the resin system. DETAILED DESCRIPTION
[0023] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0024] The following examples contain the following raw materials: hollow glass microspheres: S4630, manufacturer: 3M; sodium hydroxide (CAS: 1310-73-2); vinyl triethoxysilane (CAS: 78-08-0); ethanol (CAS: 64-17-5); 6-mercaptohexanoic acid (CAS: 17689-17-7); dichloromethane (CAS: 75-09-2); photoinitiator TPO (CAS: 75980-60-8); thionyl chloride (CAS: 7719-09-7); N,N-dimethylformamide (CAS: 68-12-2); aluminum chloride (CAS: 7446-70- 0); 2,2'-diallylbisphenol A (CAS: 1745-89-7); bismaleimide (CAS: 13676-54-5); bisphenol A cyanate (CAS: 1156-51-0); epoxy resin: KDP-550MC65, manufacturer: KUKDO; linear phenolic resin (CAS: 65733-76-8); 2-ethyl 4-methylimidazole (CAS: 23996-25-0); acetone (CAS: 67-64-1); 8-mercaptooctanoic acid (CAS: 74328-61-3); vinyltrimethoxysilane (CAS: 2768-02-7).
[0025] Example 1: Step 1: Preparation of DBA-modified hollow glass microspheres: (1) Add the hollow glass microspheres to 40% sodium hydroxide solution, continue stirring, react at 80°C for 2 hours, filter after cooling, wash and dry to obtain alkali-etched hollow glass microspheres; (2) Dissolve 20 parts of vinyl triethoxysilane in 80% ethanol solution, add 20 parts of alkali-etched hollow glass microspheres, continue stirring, react at 70°C for 30 minutes, filter after cooling, wash and dry to obtain modified hollow glass microspheres A; (3) Mix 20 parts of 6-mercaptohexanoic acid and 20 parts of modified hollow glass microspheres A and add dichloromethane; (4) adding 10 parts of modified hollow glass microspheres B to ethanol, after ultrasonic dispersion, adding 5 parts of aluminum chloride and 20 parts of 2,2'-diallyl bisphenol A, stirring and reacting at 55°C for 12 hours, filtering, washing with ethanol, and obtaining DBA modified hollow glass microspheres;
[0026] Step 2: Preparation of semi-cured sheet: (1) Add 40 parts of DBA-modified hollow glass microspheres to acetone, add 20 parts of 2,2′-diallyl bisphenol A after ultrasonic dispersion, stir and ultrasonically disperse for 1 hour, add 35 parts of bismaleimide and 60 parts of bisphenol A type cyanate, heat until melted, raise the temperature to 150°C and continue stirring, react for 30 minutes to obtain BT resin prepolymer; (2) Dissolve 100 parts of BT resin prepolymer, 20 parts of epoxy resin, 5 parts of linear phenolic resin, and 1 part of 2-ethyl 4-methylimidazole in 20 parts of acetone to obtain a prepreg, immerse the fiberglass cloth in the prepreg for 10 minutes, take it out and cure it at 130°C for 3 hours to obtain a semi-cured sheet;
[0027] Step 3: Preparation of BT resin-based copper clad laminate: Stack 5 semi-cured sheets and cover them with copper foil on both sides. Keep them at 150°C and 0.6Mpa in a vacuum press for 1 hour, increase the temperature and pressure to 180°C and 1Mpa for 2 hours, and finally increase the temperature and pressure to 200°C and 2Mpa for 2 hours for curing. After cooling, a BT resin-based copper clad laminate is obtained.
[0028] Example 2: Step 1: Preparation of DBA-modified hollow glass microspheres: (1) Add the hollow glass microspheres to 40% sodium hydroxide solution, continue stirring, react at 80°C for 2 hours, filter after cooling, wash and dry to obtain alkali-etched hollow glass microspheres; (2) Dissolve 20 parts of vinyl triethoxysilane in 80% ethanol solution, add 20 parts of alkali-etched hollow glass microspheres, continue stirring, react at 70°C for 30 minutes, filter after cooling, wash and dry to obtain modified hollow glass microspheres A; (3) Mix 20 parts of 8-mercaptooctanoic acid and 20 parts of modified hollow glass microspheres A and add dichloromethane; (4) adding 10 parts of modified hollow glass microspheres B to ethanol, after ultrasonic dispersion, adding 5 parts of aluminum chloride and 20 parts of 2,2'-diallyl bisphenol A, stirring and reacting at 55°C for 12 hours, filtering, washing with ethanol, and obtaining DBA modified hollow glass microspheres;
[0029] Step 2: Preparation of semi-cured sheet: (1) Add 40 parts of DBA-modified hollow glass microspheres to acetone, add 20 parts of 2,2′-diallyl bisphenol A after ultrasonic dispersion, stir and ultrasonically disperse for 1 hour, add 35 parts of bismaleimide and 60 parts of bisphenol A type cyanate, heat until melted, raise the temperature to 150°C and continue stirring, react for 30 minutes to obtain BT resin prepolymer; (2) Dissolve 120 parts of BT resin prepolymer, 15 parts of epoxy resin, 5 parts of linear phenolic resin, and 1 part of 2-ethyl 4-methylimidazole in 20 parts of acetone to obtain a prepreg, immerse the fiberglass cloth in the prepreg for 10 minutes, take it out and cure it at 130°C for 3 hours to obtain a semi-cured sheet;
[0030] Step 3: Preparation of BT resin-based copper clad laminate: Stack 5 semi-cured sheets and cover them with copper foil on both sides. Keep them at 150°C and 0.6Mpa in a vacuum press for 1 hour, increase the temperature and pressure to 180°C and 1Mpa for 2 hours, and finally increase the temperature and pressure to 200°C and 2Mpa for 2 hours for curing. After cooling, a BT resin-based copper clad laminate is obtained.
[0031] Example 3: Step 1: Preparation of DBA-modified hollow glass microspheres: (1) Add the hollow glass microspheres to 40% sodium hydroxide solution, continue stirring, react at 80°C for 2 hours, filter after cooling, wash and dry to obtain alkali-etched hollow glass microspheres; (2) Dissolve 40 parts of vinyltrimethoxysilane in 80% ethanol solution, add 20 parts of alkali-etched hollow glass microspheres, continue stirring, react at 70°C for 30 minutes, filter after cooling, wash and dry to obtain modified hollow glass microspheres A; (3) Mix 40 parts of 6-mercaptohexanoic acid and 20 parts of modified hollow glass microspheres A and add dichloromethane; (4) adding 10 parts of modified hollow glass microspheres B to ethanol, after ultrasonic dispersion, adding 5 parts of aluminum chloride and 20 parts of 2,2'-diallyl bisphenol A, stirring and reacting at 55°C for 12 hours, filtering, washing with ethanol, and obtaining DBA modified hollow glass microspheres;
[0032] Step 2: Preparation of semi-cured sheet: (1) Add 40 parts of DBA-modified hollow glass microspheres to acetone, add 20 parts of 2,2′-diallyl bisphenol A after ultrasonic dispersion, stir and ultrasonically disperse for 1 hour, add 35 parts of bismaleimide and 60 parts of bisphenol A type cyanate, heat until melted, raise the temperature to 150°C and continue stirring, react for 30 minutes to obtain BT resin prepolymer; (2) Dissolve 80 parts of BT resin prepolymer, 50 parts of epoxy resin, 10 parts of linear phenolic resin, and 3 parts of 2-ethyl 4-methylimidazole in 30 parts of acetone to obtain a prepreg, immerse the fiberglass cloth in the prepreg for 10 minutes, take it out and cure it at 130°C for 3 hours to obtain a semi-cured sheet;
[0033] Step 3: Preparation of BT resin-based copper clad laminate: Stack 5 semi-cured sheets and cover them with copper foil on both sides. Keep them at 150°C and 0.6Mpa in a vacuum press for 1 hour, increase the temperature and pressure to 180°C and 1Mpa for 2 hours, and finally increase the temperature and pressure to 200°C and 2Mpa for 2 hours for curing. After cooling, a BT resin-based copper clad laminate is obtained.
[0034] Comparative Example 1: Step 1: Preparation of prepreg: (1) Add hollow glass microspheres to 40% sodium hydroxide solution, continue stirring, react at 80°C for 2 hours, filter after cooling, wash and dry to obtain alkali-etched hollow glass microspheres; (2) Dissolve 20 parts of vinyl triethoxysilane in 60% ethanol solution, add 20 parts of alkali-etched hollow glass microspheres, continue stirring, react at 80°C for 3 hours, filter after cooling, wash and dry to obtain silane coupling agent modified hollow glass microspheres; (3) Add 40 parts of silane coupling agent modified hollow glass microspheres to acetone , add 20 parts of 2,2′-diallyl bisphenol A after ultrasonic dispersion, stir and ultrasonically disperse for 1 hour, add 35 parts of bismaleimide and 60 parts of bisphenol A type cyanate, heat until melted, raise the temperature to 150°C and continue stirring, react for 30 minutes to obtain BT resin prepolymer; (4) dissolve 100 parts of BT resin prepolymer, 20 parts of epoxy resin, 5 parts of linear phenolic resin, and 1 part of 2-ethyl 4-methylimidazole in 20 parts of acetone to obtain a prepreg, immerse the fiberglass cloth in the prepreg for 10 minutes, take it out and cure it at 130°C for 3 hours to obtain a semi-cured sheet;
[0035] Step 2: Preparation of BT resin-based copper clad laminate: stack 5 semi-cured sheets and cover them with copper foil on both sides, keep them at 150℃ and 0.6Mpa in a vacuum press for 1 hour, increase the temperature and pressure to 180℃ and 1Mpa for 2 hours, and finally increase the temperature and pressure to 200℃ and 2Mpa for 2 hours to cure, and obtain BT resin-based copper clad laminate after cooling.
[0036] Comparative Example 2: The number of 6-mercaptohexanoic acid parts in step 1 (3) is changed to 5 parts, and the rest is the same as in Example 1.
[0037] Comparative Example 3: Step 1: Preparation of DBA-modified graphene oxide: (1) 0.5 parts of graphene oxide, 200 parts of thionyl chloride, and 20 parts of N,N-dimethylformamide were mixed evenly, and condensed and refluxed at 70° C. for 12 hours. After washing and drying, thionyl chloride-modified graphene oxide was obtained; (2) thionyl chloride-modified graphene oxide was added to ethanol, and after ultrasonic dispersion, 2 parts of aluminum chloride and 10 parts of 2,2'-diallylbisphenol A were added, and the mixture was stirred and reacted at 55° C. for 12 hours. After filtering, the mixture was washed with ethanol and dried to obtain DBA-modified graphene oxide;
[0038] Step 2: Preparation of semi-cured sheet: (1) Add 1 part of DBA-modified graphene oxide to acetone, add 20 parts of 2,2′-diallyl bisphenol A after ultrasonic dispersion, stir and ultrasonic disperse for 1 hour, add 35 parts of bismaleimide and 60 parts of bisphenol A type cyanate, heat until melted, raise the temperature to 150°C and continue stirring, react for 30 minutes to obtain BT resin prepolymer; (2) Dissolve 100 parts of BT resin prepolymer, 20 parts of epoxy resin, 5 parts of linear phenolic resin, and 1 part of 2-ethyl 4-methylimidazole in 20 parts of acetone to obtain a prepreg, immerse the fiberglass cloth in the prepreg for 10 minutes, take it out and cure it at 130°C for 3 hours to obtain a semi-cured sheet;
[0039] Step 3: Preparation of BT resin-based copper clad laminate: Stack 5 semi-cured sheets and cover them with copper foil on both sides. Keep them at 150°C and 0.6Mpa in a vacuum press for 1 hour, increase the temperature and pressure to 180°C and 1Mpa for 2 hours, and finally increase the temperature and pressure to 200°C and 2Mpa for 2 hours for curing. After cooling, a BT resin-based copper clad laminate is obtained.
[0040] Test experiment 1: The dielectric constants of the examples and comparative samples were tested according to GB / T 4722-2017; the bending properties of the copper clad laminate were tested according to GB / T9341-2008. The experimental data are as follows:
[0041] Test items Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Comparative Example 3 Dielectric constant 2.84 2.81 2.89 3.01 2.91 3.15 Bending strength(MPa) 253.1 249.7 256.5 210.7 223.8 231.4
[0042] Conclusion: From the data analysis of Examples 1 to 3 in the table, it can be seen that the dielectric properties of the copper clad laminate are improved with the introduction of DBA-modified hollow glass microspheres, and the toughness of the copper clad laminate is good; the results of Examples 1 to 3 and Comparative Example 1 show that the DBA-modified hollow glass microspheres have better compatibility and interface bonding ability with the BT resin system than those modified with ordinary silane coupling agents. This is because DBA can react with bismaleimide to increase the chain length of bismaleimide, so the toughness is better; the results of Examples 1 to 3 and Comparative Example 2 show that in the preparation process of DBA-modified hollow glass microspheres, mercapto acid with too low a mass fraction will affect the toughness of the copper clad laminate. This is because mercapto acid reacts with vinyl silane coupling agent to introduce carboxyl groups on the surface of hollow glass microspheres, which provides conditions for subsequent acyl chlorination and grafting of DBA. Too low a proportion of mercapto acid will make the DBA content on the surface of the final modified hollow glass microspheres insufficient, thereby affecting the dispersibility of the hollow glass microspheres and the interface compatibility of the resin. In addition, mercapto acid Acid can also play a chain extension effect in DBA. DBA with a longer chain length can improve the overall toughness of the resin after reacting with bismaleimide. The results of Examples 1 to 3 and Comparative Example 3 show that the copper-clad laminate with DBA-modified hollow glass microspheres has better dielectric properties and toughness than the copper-clad laminate with DBA-modified graphene oxide. This is because the hollow glass microspheres are spherical structures. Therefore, after modification, the hollow glass microspheres can capture more DBA on the surface compared to the flaky graphene oxide, which makes it have a better dispersion effect in the BT resin system. Secondly, the spherical structure makes the interaction between the particles of the hollow glass microspheres small. Thanks to the "ball effect", the friction is smaller, and it has better fluidity and dispersibility, so it can provide better toughness. On the other hand, when a certain amount of graphene oxide is added to the resin system, local agglomeration is prone to occur, thereby affecting the mechanical properties of the material. In contrast, the hollow glass microspheres can be added in a higher amount in the resin system, so their dielectric properties are also better.
[0043] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a high-frequency and high-speed BT resin-based copper-clad laminate, characterized in that: The following steps are involved: Step 1: Preparation of DBA-modified hollow glass microspheres: (1) treating the hollow glass microspheres with sodium hydroxide solution and silane coupling agent to obtain modified hollow glass microspheres A; (2) adding the modified hollow glass microspheres A and mercapto acid into dichloromethane, adding 0.1-0.8 wt% of photoinitiator after dispersion, stirring evenly and irradiating with ultraviolet light for 10-60 seconds, filtering and washing with ethanol, mixing the obtained product with thionyl chloride and N,N-dimethylformamide evenly, condensing and refluxing at 40-80° C. for 8-16 hours, washing and drying to obtain modified hollow glass microspheres B; (3) adding the modified hollow glass microspheres B, aluminum chloride and 2,2'-diallylbisphenol A into ethanol, and obtaining DBA-modified hollow glass microspheres after reaction; Step 2: Preparation of prepreg: (1) DBA-modified hollow glass microspheres, 2,2'-diallyl bisphenol A, bismaleimide, and bisphenol A cyanate are mixed, and a BT resin prepolymer is obtained after a temperature reaction is completed; (2) BT resin prepolymer, epoxy resin, curing agent, and curing accelerator are dissolved in a solvent to obtain a prepreg, and a glass fiber cloth is impregnated in the prepreg and then heated and cured to obtain a prepreg; Step 3: Preparation of BT resin-based copper clad laminate: after laminating the prepregs in multiple layers, cover both sides with copper foil, press them in a vacuum press, and obtain BT resin-based copper clad laminate after cooling; In step 1 (1), the silane coupling agent is a vinyl silane coupling agent; In step 1 (2), the mass ratio of the modified hollow glass microsphere A, mercapto acid, thionyl chloride and N,N-dimethylformamide is 1:(1-3):(20-30):(1-3).
2. The method for preparing a high-frequency and high-speed BT resin-based copper-clad laminate according to claim 1, characterized in that: In step 1 (1), the concentration of the sodium hydroxide solution is 30-70%, and the mass ratio of the silane coupling agent to the hollow glass microspheres is (1-2):
1.
3. The method for preparing a high-frequency and high-speed BT resin-based copper-clad laminate according to claim 1, characterized in that: In step 1 (3), the specific process is: adding the modified hollow glass microspheres B to ethanol, after ultrasonic dispersion, adding aluminum chloride and 2,2'-diallyl bisphenol A, reacting at 40-60° C. for 10-15 hours, filtering, washing and drying to obtain DBA modified hollow glass microspheres; wherein the mass ratio of the modified hollow glass microspheres B, aluminum chloride and 2,2'-diallyl bisphenol A is (2-3): (1-1.5): (4-6).
4. The method for preparing a high-frequency and high-speed BT resin-based copper-clad laminate according to claim 1, characterized in that: In step 2 (1), the specific process is: add DBA modified hollow glass microspheres to acetone, add 2,2'-diallyl bisphenol A after ultrasonic dispersion, stir and ultrasonically disperse for 1 hour, add bismaleimide and bisphenol A type cyanate in sequence, heat until melted, raise the temperature to 120-180°C and continue stirring, react for 20-50 minutes to obtain BT resin prepolymer; the mass ratio of the DBA modified hollow glass microspheres, 2,2'-diallyl bisphenol A, bismaleimide and bisphenol A type cyanate is (2-8): (4-8): (6-8): (10-15).
5. The method for preparing a high-frequency and high-speed BT resin-based copper-clad laminate according to claim 1, characterized in that: In step 2 (2), the components of the prepreg include: in parts by weight: 80 to 120 parts of BT resin prepolymer, 15 to 50 parts of epoxy resin, 5 to 15 parts of curing agent, 1 to 5 parts of curing accelerator, and 10 to 30 parts of solvent; the glass fiber cloth is impregnated in the prepreg for 5 to 20 minutes; the curing temperature is 120 to 140° C., and the curing time is 2 to 5 hours.
6. The method for preparing a high-frequency and high-speed BT resin-based copper-clad laminate according to claim 5, characterized in that: The curing agent includes one or more of dicyandiamide and phenolic resin; the curing accelerator is an imidazole accelerator; and the solvent includes one of acetone, butanone, cyclohexanone and dimethylformamide.
7. The method for preparing a high-frequency and high-speed BT resin-based copper-clad laminate according to claim 1, characterized in that: In step three, the specific temperature and pressure during the pressing process are: increase the temperature and pressure to 150-160°C, 0.5-0.8Mpa, and maintain for 1-1.5h, then increase the temperature and pressure to 170-190°C, 0.9-1.2Mpa, and maintain for 1.5-2h, and finally increase the temperature and pressure to 190-220°C, 1.8-2.2Mpa, and maintain for 1.5-2h.
8. A BT resin-based copper-clad laminate prepared according to the method for preparing a high-frequency and high-speed BT resin-based copper-clad laminate according to any one of claims 1 to 7.
Citation Information
Patent Citations
High-temperature-resistant alkynyl monomaleimide modified bismaleimide resin and preparation method thereof
CN107523055A
Modified BT resin and preparation method thereof
CN115873406A